Review: Aplikasi Histopatologi Untuk Praktik Forensik: Review: Applications of Histopathology for Forensic Practice - Faulana, Arum Fahmi; Empra, Desi Eka Putri; Rahmadian, Desti; Shalihah, Fianicha; Nuriliani, Ardaning; Retnoaji, Bambang; Saragih, Hendry Tri Sakti SG; Rohmah, Zuliyati; Septriani, Nur Indah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Forensics plays an important role in investigating crimes because it can reveal everything related to a murder case, including the time and cause of the murder. Histopathology is the study of damage to body tissues and organs which can be used to help investigate crimes. The aim of this literature review is to study the role of histopathology applications for forensic practice. The method used is searching journals and books using Google Scholar, ScienceDirect, NCBI, and PubMed with the keywords histopathology, forensics, diagnosis, death, microscopy, disease, staining, and autopsy. The histology approach helps the pathologist make a clear determination on the cause of death. The aim of histopathology is to perfect the macroscopic diagnosis and act as an additional examination in forensic case management. One of the histopathology methods in the forensic field is the paraffin method with hematoxylin eosin staining and special stains, immunohistochemistry, and MITS. The parameters observed with this method are measurements of pulmonary fat embolism; determining the age of myocardial infarction; assessment of liver steatosis, fibrosis, and cirrhosis; determination of the age of thrombus or thromboembolism; and diagnosis of shock with various diseases. The prospect of forensic histopathology is to complement molecular diagnostic methods, so that the combination of molecular and histology methods can play a maximum role in the field of forensic pathology. The conclusion of this literature review is that histopathology can be used to confirm the diagnosis in forensic cases and has good future prospects if combined with other methods such as molecular.